Answer:
blurd po
Step-by-step explanation:
^_________^^_________^^_________^
What is p-m pn equal to? Is it’s pm/n
Answer:
cot x = 1
Step-by-step explanation:
Answer:
Step-by-step explanation:
Comment
Expand the second and 3rd factors first. Then worry about the x.
Solution
x(x + 2)(x + 4)
<em>first</em>: x * x = x^2
<em>Outside</em>: 4*x = 4x
<em>Inside</em>: 2*x = 2x
<em>Last:</em> 2*4 = 8
Combine
x^2 + 4x + 2x + 8
x^2 + 6x + 8
Now is the time to worry about the extra x
x(x^2 + 6x + 8)
remove the brackets.
x*x^2 + x*6x + 8*x
Combine
Answer: x^3 + 6x^2 + 8x